FACTORS OF SUSTAINABLE DEVELOPMENT OF REGIONAL ECONOMY THROUGH SMALL BUSINESS DEVELOPMENT (Marketing Journal, 2025)
This article provides a comprehensive analysis of the issues related to the innovative development of small businesses. It highlights the vital role of small enterprises in advancing economic growth through innovation and their contribution to socio -econom ic stability. The paper also classifies and describes the key constraints hindering small business activities and offers practical recommendations for overcoming them. The research is based on the analysis of legal and regulatory frameworks and factor clas sification, leading to evidence -based conclusions. The authors justify the potential for accelerating regional economic growth by strengthening the institutional support for small business development. 367
Keywords: small business; innovative development; limiting factors; economic policy; state support; institutional mechanisms